Brasilidades contemporâneas: hibridismos culturais na arte brasileira (1965-2005) - Campos, Marcelo (2005)
The objective of this thesis is to place the idea of a Brazilian identity through the reappropriations of the contemporary art made in the country according to the concepts of popular, erudite and mass media. To accomplish this, it is necessary to select and analyze works in the Brazilian artistic production which make use of material culture objects, bearing the three concepts in mind, and to later organize them according to thematic axes such as: the urban space and its contradictions, the deviation from the pattern in the trajectories of anti-heroes; authoritarianism and submission; folk religiosity; intermediation of memory. The central hypothsis of the investigation consists of attributing a notable presence to the idea of a Brazilian identity in the current art of the nation, although it may be quite surprising when applied to some artists. The idea of attributing a Brazilian face to its contemporary production springs from the points which have been recurrent in various epochs of the Brazilian art history and which end up to associate, thus creating a Brazilian identity. This information would arise from processes which could be called cultural hybridisms. It is worth emphasizing that the formation of visual images and the choices of specific references to making of art are linked to a certain cultural system. Although the artists have denied to assume a programmatic vision such as the one derived from the Semana de Arte Moderna ("Week of Modern Art"), an event held in São Paulo in 1922, and from studies of folklore, the presence of motifs of the national life is self-evident in contemporary works.